2018
DOI: 10.1002/ptr.6042
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds from the African medicinal plant Cleistochlamys kirkii as resistance modifiers in bacteria

Abstract: Cleistochlamys kirkii (Benth) Oliv. (Annonaceae) is a medicinal plant traditionally used in Mozambique to treat infectious diseases. The aim of this study was to find resistance modifiers in C. kirkii for Gram-positive and Gram-negative model bacterial strains. One of the most important resistance mechanisms in bacteria is the efflux pump-related multidrug resistance. Therefore, polycarpol (1), three C-benzylated flavanones (2-4), and acetylmelodorinol (5) were evaluated for their multidrug resistance-revertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The MICs of N. sativa EO and its bioactive compounds were determined according to the Clinical and Laboratory Standard Institute guidelines in three independent assays (Kincses et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The MICs of N. sativa EO and its bioactive compounds were determined according to the Clinical and Laboratory Standard Institute guidelines in three independent assays (Kincses et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Lactone represents an important antibacterial pharmacophore which can bind with tyrosyl‐tRNA synthetase . Hence, coupling of lactone derivatives with fluoroquinolones gave a series of novel multi‐target hybrids . This study indicated that fluoroquinolone moieties influenced the antibacterial activity greatly, and ciprofloxacin was optimal for activity .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 94%
“…Lactone represents an important antibacterial pharmacophore which can bind with tyrosyl‐tRNA synthetase . Hence, coupling of lactone derivatives with fluoroquinolones gave a series of novel multi‐target hybrids .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…Disk diffusion is a simple method for screening the susceptibility of various microorganisms against drugs/candidate molecules: it is user-friendly, and there is a lot of experience accumulated due to its use in routine clinical microbiology. Disk-diffusion based QS-inhibitory (DDBQSI) assay utilizing QS-signal molecule producing strains and signal molecule-reporter strains (e.g., Agrobacterium, Chromobacterium, Pseudomonas, Serratia and Vibrio species) is the most frequently used method [36][37][38][39][40]. The advantage of this method is its simple execution, the highthroughput nature and its usability in resourcescarce settings [41].…”
Section: Figure 1 Examples Of Quorum Sensing Signal Molecules (Autoinmentioning
confidence: 99%